Virtuous Legislation: The Royal Decree for the Sustainable Management of the Woods of Serra San Bruno, Stilo, Mongiana, and Ferdinandea - Ghezzi, Renato; Fiorenza, Elia (European Scientific Journal, ESJ, 2024)
The Saving Forests Decree of 1773, issued by Ferdinand IV of Bourbon, marked a fundamental step in the sustainable management of the forests of the Serre Calabresi. Metal mining and processing in the region dates back to ancient times, with Greek colonies exploiting local resources for tools and coins. With the arrival of the Normans, the mines became strategic and were granted to the Carthusian monks, and the Norman smelting furnace improved military production. Under Ferdinand II, the Ferdinandea foundry reached its peak, producing high-quality weapons. The Salvaboschi decree demonstrated a growing awareness of the need to balance industrial needs with environmental protection. This study analyzes the decree, examining how its provisions are in line with modern environmental protection laws. The analysis of this study focuses on the provisions of the Salvaboschi decree and their compliance with current environmental protection laws. The main objective of the decree was to implement sustainable forestry practices through regulated logging cycles to prevent deforestation and promote natural regeneration. Analysis of the law reveals its progressive nature and its conformity with modern principles of environmental conservation. This historic legislation testifies to the early recognition of the importance of sustainable resource management and the foresight of the Bourbon administration in implementing practices that would benefit both the environment and industrial development. Through the study and analysis of the rules present in the document, it was possible to make significant comparisons with the laws in force. The decree demonstrates considerable foresight in the protection of natural and forest heritage. This document represents an important step towards environmental protection, highlighting a concrete and proactive commitment to the protection of natural resources. The ability to compare existing regulations with new provisions offers a clear and in-depth perspective on legislative evolution in environmental matters, confirming the importance of regulatory updates to address contemporary ecological challenges.